TEKNIK SKARIFIKASI PERCEPATAN DAN PENINGKATAN DAYA KECAMBAH BENIH SENGON BUTO (Enterolobium cyclocarpum) - Muhamad Hidayatulah; Yudi Firmanul Arifin; Susilawati Susilawati (Lambung Mangkurat University-Indonesia, 2019)
The demand for wood from sengon buto from year to year is always increasing. This species is also often used for revegetation after coal mining, because its ability to adapt to nutrient-poor soils is very high. Therefore this plant must be cultivated to fulfill these demands. But the scarification ability of sengon buto seeds is very low, so the sprout power scarification technique is needed. This study aims to accelerate the process of scarification and increasing in sengon buto sprout power. The treatment was used by soaking with hot water at 100oC for 5 minutes, water at room temperature for 24 hours and without immersion, each treatment as many as 50 seeds. The treated seeds were planted each in a greenhouse, under paranet and without shade. The parameters were measured the percentage of life, increase in number of leaves and height increase. This study was analyzed using a factorial 3 x 3 Complete Random Design with 50 samples. The results showed that the highest percentage of germination power with immersion of hot water was found in greenhouses of 52%, soaking in water with room temperature of 16% and without immersion of 24%. The value of germination percentage with treatment under paranet with the highest immersion in hot water is 44%, water immersion with room temperature of 34% and without immersion of 14%. Furthermore, the value of germination percentage in the open place with hot water immersion by 40%, water immersion with room temperature of 8% and without immersion of 28%.